2009
DOI: 10.1007/s10562-009-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Nano Nickel Particles over SBA-15 Modified by Carbon Films on Pore Walls

Abstract: Mesoporous SBA-15 was prepared by using P123 as a template. The precursor with the template was calcined in an inert atmosphere so that carbon films might be formed in pores of SBA-15 due to the decomposition of template. The SBA-15C thus formed contained 3% C and exhibited similar pore structures as the SBA-15. Both SBA-15 and SBA-15C were used to support 20% nickel (by weight) via impregnation. It was found that doping with carbon films enhanced the dispersion of supported nickel. However, calcination at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…They found that the coke is difficult to be formed on its surface and metal sintering rate is also slow. Nickel metal sometimes showed the similar catalytic activity as some noble metals such as Pt and Pd [17,24]. Rh is found to have higher catalytic performance and coke resistant ability than Ni in the steam reforming of tar, but it is limited by its high cost for large-scale applications [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the coke is difficult to be formed on its surface and metal sintering rate is also slow. Nickel metal sometimes showed the similar catalytic activity as some noble metals such as Pt and Pd [17,24]. Rh is found to have higher catalytic performance and coke resistant ability than Ni in the steam reforming of tar, but it is limited by its high cost for large-scale applications [25].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the support materials with low surface area (mostly less than 200 m 2 /g) easily lead to the sintering of supported metal during the thermal treatment period due to low dispersion with high accumulation of metal [31]. Recently, mesoporous molecular sieves such as HMS, KIT-1, SBA-15 and MCM-41 with high BET surface area have been attracted considerable interest as catalyst supports [24,32]. Among them, MCM-41 is widely utilized 5 as adsorbents, catalyst support and hydrogenation catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the strong interactions of iron species with Al 2 O 3 , it would be easy to prepare the catalyst with highly dispersed iron species. In addition, a small amount of carbon was added into the Fe/Al 2 O 3 in order to promote the reduction of supported iron species [16] . Then, the…”
Section: Introductionmentioning
confidence: 99%
“…The low adsorption capacity was another drawback for this type of adsorbents. Among the commercial adsorbents involving π-complexation mechanism, such as activated carbon, Y molecular sieve, 13X molecular sieve and 4A molecular sieve, , carbon molecular sieve , and silica gel, mesoporous silica materials appears to be the promising candidates for olefins and paraffins separation due to its features of large specific surface areas, narrow pore size distribution, adaptable pore size, and facile functionalization. As an example, mesoporous adsorbent Ag-MCM-41 was successfully applied to the separation of propane and propylene by forming CC complexation with olefins …”
Section: Introductionmentioning
confidence: 99%